Effect of the pacing strategies on the open-water 10-km World Swimming Championships performances - Rodriguez, L.; Veiga, S. (International Journal of Sports Physiology and Performance, 2018)
Purpose: To (1) compare the pacing strategies of different-level open-water swimmers during the 10-km race of the FINA 2015 Swimming World Championships and (2) relate these pacing strategies to the race performance. Methods: Final and intermediate split times, as well as intermediate race positions, from the 10-km race participants (69 men and 51 women) were collected from the public domain and were divided into 5 groups (G1-G5) depending on their finishing positions. Results: Medalists and finalists (G1 and G2, respectively) presented an even pacing profile with swimming velocities similar to those of the less successful swimmers (G3-G5) on the initial and middle stages of the race but a 1.5-3% increase in swimming velocity in the last quarter of the race. This acceleration toward the end of the race, or "end spurt," was largely related to the race performance and was not observed in the G3 and G4 (even-paced profile) or G5 (positive pacing profile) groups. Intermediate race positions and lap rankings were negatively related to finishing position, indicating a delayed positioning of the most successful swimmers at 25%, 50%, and 75% of race distance. Conclusions: The adoption of a conservative starting strategy by open-water swimmers with a negative pacing profile and delayed partial positioning seems to increase the chances of overall race success, as it allows a fast end spurt that is closely related to successful finishing race positions.